Construction dispute resolution handbook - Gaitskell, Robert; Gaitskell, Robert (ICE, 2011)
The "Construction Dispute Resolution Handbook" provides construction professionals and lawyers with straightforward and pragmatic advice on dealing with construction disputes, at all stages, using principles that are applicable internationally.